Perlindungan Hukum atas Data Pribadi Konsumen dalam Kegiatan Ekonomi Digital di Indonesia - Sheilla Rahima Agustin; Sodikin Sodikin (AHKAM, 2026)
Technological development and digital transactions in Indonesia have facilitated economic activities for society, but at the same time have created risks of personal data breaches that may harm consumers and threaten the privacy rights of digital platform users. This study aims to analyze the effectiveness of legal protection for consumers’ personal data in the digital transaction system in Indonesia. This study uses a normative legal method with statutory and conceptual approaches through library research. The results show that legal protection for personal data has been regulated in Law Number 27 of 2022 on Personal Data Protection and the Electronic Information and Transactions Law; however, its implementation still faces various obstacles, particularly weak supervision of electronic system providers, suboptimal law enforcement, low levels of public digital literacy, and increasing cybersecurity threats in line with the development of information technology. The conclusion of this study emphasizes that legal protection for consumers’ personal data in digital transactions has not been fully effective because there remains a gap between regulation and its practical implementation. The implications of this study indicate the need to strengthen supervision, optimize law enforcement, improve public digital literacy, and enhance digital system security so that consumer personal data protection can be implemented more effectively.